Influence of the height of prismatic workpieces on stress distribution during compression with cylindrical tools - Vilotić, Dragiša (Journal of Production Engineering, 2023)
In this study, the influence of the initial geometry of the workpieces on the stress components during the milling of parallelepipeds with cylindrical tools and on the stress state parameter (forming capacity of the workpiece) is analyzed. Simultaneously, the effect of the workpiece height on the force-displacement diagram was investigated. The stress state was examined using the strip method, and the determination of the force-displacement diagrams was carried out experimentally.